(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
The article is based on the fact that the green economy is an important direction determining the future of our country. The article examines the theoretical issues of the green economy and develops its definition. Seven priority tasks are defined for the formation of this economy.